Strategic Capabilities and Their Role in Enhancing Organizational Ambidexterity An Analytical Study in the Directorate of Rutba Municipality - Awad, Mahmood J. (Technium Business and Management, 2025)
The research aims to identify the role of strategic capabilities as an independent variable in enhancing organizational ambidexterity as a dependent variable in the Directorate of Rutba Municipality. The researcher sought to introduce the organization’s management to the importance of these capabilities, highlight their role in strengthening organizational ambidexterity, and determine whether these capabilities positively or negatively impact performance. The researcher adopted a descriptive analytical approach to conduct the study by testing several main and sub-hypotheses to examine the correlation and impact relationships between the variables, aiming to answer the research problem’s questions. The researcher relied on the questionnaire as a main tool in collecting and analyzing the data obtained from the respondents working in the directorate, as a random intentional sample was chosen from the organization, where the researcher distributed (67) questionnaires within the organization and (63) questionnaires were retrieved, (2) of which were not suitable for statistical analysis, leaving 61 of them representing (leaders and officials of administrative units, engineers and technicians) working in the directorate. The data were analyzed using the statistical program (SPSS), through the use of a set of statistical methods such as (weighted arithmetic mean, standard deviation, coefficient of variation, and relative importance), in addition to testing the hypotheses of association and influence at the level of variables and their dimensions. The research reached a set of conclusions, the most important of which is a direct correlation with statistical significance between strategic capabilities and their dimensions in organizational ambidexterity in the Rutba Municipality Directorate. This means there is a clear interest on the part of the directorate’s administrations in their capabilities, which reflects their ability to employ them correctly to achieve organizational ambidexterity for their directorate.